Design and fabrication of microfluidic food spoilage sensor - Sim, Yan Lim (2014)
Microfluidic paper-based devices (micropads) are an advancing research area offering real-time analysis which utilizes only microlitre volumes of fluids. The main advantages of using paper as the detection platform include its affordability, portability and ease of use. Paper transports fluid based on capillary action and does not require additional devices.